Variation in whole-rotation yield among Eucalyptus genotypes in response to water and heat stresses: The TECHS project - Binkley, Dan; Campoe, Otavio C. [UNESP]; Alvares, Clayton Alcarde [UNESP]; Carneiro, Rafaela Lorenzato; Stape, Jose L. [UNESP] (Elsevier, 2020)
The TECHS project spanned a 3500 km gradient from the Amazon to Uruguay, examining the influence of stresses from temperature and water supply on clonal plantations of Eucalyptus, with and without rain reduction, and across a stocking gradient. The whole-rotation mean annual increment (MAI) showed a humped pattern in relation to temperature, rising from about 18 Mg ha−1 yr−1 of stemwood production when mean annual temperatures were near 16 °C, to 27 Mg ha−1 yr−1 at 20 °C, and then falling to less than 15 Mg ha−1 yr−1 above 24 °C. The age trend in growth showed a steeper initial rise in the warmer tropical sites (reaching a peak current annual increment, CAI, of 27 Mg ha−1 yr−1, at age 2–3 years), but the slower early growth in the cooler subtropical sites had a higher peak (CAI of 32 Mg ha−1 yr−1, at 4 years) and slower decline, giving 15% higher MAI for the cooler region. Whole-rotation MAI declined by about 2.2 Mg ha−1 yr−1 for each 1 °C increase in temperature (in the range between 19.5 and 23.5 °C), and MAI declined by 0.5 Mg ha−1 yr−1 for each 100 mm yr−1 decline in rain. The effect of reducing ambient rain was also a loss of 0.5 Mg ha−1 yr−1 for each 100 mm yr−1 reduction in rain, though the effect was small on low productivity sites (<0.1 Mg ha−1 yr−1 for sites with MAI of 10 Mg ha−1 yr−1), and large on high productivity sites (1.4 Mg ha−1 yr−1 for sites with MAI of 40 Mg ha−1 yr−1). In the stocking portion of the project, growth of individual trees decreased (and stand-level growth increased) with increases in stocking, and water deficits led to decline in both measures of growth. Under favorable environments for Eucalyptus, stem growth in intensively managed plantations is about five-times the rates reported for non-plantation forests. The higher growth in plantations declines under warmer and drier conditions, matching productivity of non-plantation forests below about 900 mm yr−1 rainfall and 26 °C annual average temperature. The potential productivity of forests depends more strongly on management systems (genetic selection, site preparation, fertilization, spacing, competition control and protection) than on environmental gradients.